Mpox knowledge, behaviours and barriers to public health measures among gay, bisexual and other men who have sex with men in the UK: a qualitative study to inform public health guidance and messaging - Tom May; Lauren Towler; Louise E Smith; Jeremy Horwood; Sarah Denford; G James Rubin; Matthew Hickman; Richard Amlôt; Isabel Oliver; Lucy Yardley (BMC, 2023)
Abstract Background The 2022-23 mpox epidemic is the first-time sustained community transmission had been reported in countries without epidemiological links to endemic areas. During that period, the outbreak almost exclusively affected sexual networks of gay, bisexual, or other men who have sex with men (GBMSM) and people living with HIV. In efforts to control transmission, multiple public health measures were implemented, including vaccination, contact tracing and isolation. This study examines knowledge, attitudes, and perceptions of mpox among a sample of GBMSM during the 2022-23 outbreak in the UK, including facilitators for and barriers to the uptake of public health measures. Methods Interviews were conducted with 44 GBMSM between May and December 2022. Data were analysed using reflexive thematic analysis. Positive and negative comments pertaining to public health measures were collated in a modified version of a 'table of changes' to inform optimisations to public health messages and guidance. Results Most interviewees were well informed about mpox transmission mechanisms and were either willing to or currently adhering to public health measures, despite low perceptions of mpox severity. Measures that aligned with existing sexual health practices and norms were considered most acceptable. Connections to GBMSM networks and social media channels were found to increase exposure to sexual health information and norms influencing protective behaviours. Those excluded or marginalized from these networks found some measures challenging to perform or adhere to. Although social media was a key mode of information sharing, there were preferences for timely information from official sources to dispel exaggerated or misleading information. Conclusions There are differential needs, preferences, and experiences of GBMSM that limit the acceptability of some mitigation and prevention measures. Future public health interventions and campaigns should be co-designed in consultation with key groups and communities to ensure greater acceptability and credibility in different contexts and communities.